(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The appeal, as a regular legal remedy, has a significant feature - the fact that a timely appeal prevents the judgment from becoming legally effective in the part challenged by the appeal. The latest civil procedure reform in Serbia, implemented in 2011, significantly changed the consequences of the appeal in procedures considering small claim disputes. In small claims - monetary claims limited to amount of 300 Euros or less, a timely appeal does not postpone the legal effectiveness of the judgment (nonsuspensory effect of the appeal). In this paper, the author analyzes the causes, as well as the consequences of this legal solution. While reason for this can be explained by the tendency toward efficiency in the procedure, the (harmful) effects of this provision, caused by judicial misinterpretations, is still to be perceived.